English Studies in the 21st Century - Antakyalioğlu, Zekiye; Asiatidou, Kyriaki; Gündüz, Ela İpek (Cambridge Scholars Publishing, 2020)
English Studies in the 21st Century presents the results of recent academic research concerning a wide spectrum of subjects--including politics, psychology, religion, philosophy, history, culture, aesthetics, and education--related to literary, cultural, and language studies. Specifically, this collection includes scholarly reflections, interpretations, criticisms, and experiments that both strengthen and challenge dominant perspectives on the English literary tradition and contribute to a multifaceted discussion of contemporary drama and theater, contemporary theory and fiction, Neo-Victorian.